Particle Micronization of Medicinal Plants Extract using Electrospraying - Nadya Rizkita; Bisma Hendra Setiyawan; Rais Fakhrirazin; Siti Machmudah; Sugeng Winardi; Wahyudiono (Universitas Muhammadiyah Purwokerto, 2026)
Phytochemical compounds are non-nutritive plant bioactive componentsthat contribute to disease prevention through their antioxidant and antiinflammatoryactivities. In this study, particles of polyvinylpyrrolidone (PVP),chitosan, and starch-containing phytochemical compounds from medicinalplant extracts were prepared through an electrospray process. This methodis used to increase the bioavailability of phytochemical compounds as wellas to facilitate the storage process and durability. The effect of processparameters in this study was investigated, the type of polymers (medicinalplant extract/PVP, chitosan, and starch) and the electric voltage used.Particle characterization and phytochemical properties were evaluated usingFTIR, total phenolic content (TPC), total flavonoid content (TFC), andantioxidant activity analyses. The results showed that PVP exhibited the bestperformance in binding phytochemical compounds from medicinal plants.This was exemplified by the O. aristatus/PVP at an applied voltage of 16 kV,which resulted in the highest total phenolic and flavonoid contents of 0.5816mg GAE/g sample and 0.7638 mg CE/g sample, respectively. Antioxidantactivity, evaluated using antioxidant efficiency (AE), also showed the highestvalue for the O. aristatus/PVP at 18 kV, reaching 0.8511 min⁻¹. FTIR analysisindicated that PVP was able to physically interact with phytochemicalcompounds, as evidenced by the overlap between the polymer and extractspectra. In contrast, chitosan and starch exhibited relatively weakerinteractions, leading to more limited encapsulation capability andconsequently lower retention of phytochemical compounds within theparticles.